2010
DOI: 10.4049/jimmunol.0902399
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Liver X Receptor Sensitizes Human Dendritic Cells to Inflammatory Stimuli

Abstract: Dendritic cells (DCs) respond to changes in their lipid environment by altering gene expression and immunophenotype. Some of these alterations are mediated via the nuclear receptor superfamily. However, little is known about the contribution of liver X receptor (LXR) to DC biology. In this study, we present a systematic analysis of LXR, activated by synthetic ligands or naturally occurring oxysterols in developing human monocyte-derived DCs. We found that LXRs are present and can be activated throughout DC dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 44 publications
4
46
1
Order By: Relevance
“…6 Similarly, pretreatment with the LXR agonist was shown to sensitize human dendritic cells to LPS stimulation. 7 These differential effects in mouse and human cells were clearly observed in the present study. Indeed and in sharp contrast to human macrophages, LXR treatment significantly decreased eicosanoid secretion in mouse macrophages.…”
Section: Ishibashi Et Al Lxr Regulates Lpcat3 and Arachidonate Metabosupporting
confidence: 75%
“…6 Similarly, pretreatment with the LXR agonist was shown to sensitize human dendritic cells to LPS stimulation. 7 These differential effects in mouse and human cells were clearly observed in the present study. Indeed and in sharp contrast to human macrophages, LXR treatment significantly decreased eicosanoid secretion in mouse macrophages.…”
Section: Ishibashi Et Al Lxr Regulates Lpcat3 and Arachidonate Metabosupporting
confidence: 75%
“…LXR-␣ activation takes place upon ligand binding that leads to a molecular switch replacing a corepressor by a coactivator complex ( 35 ). Previous studies showed that adding exogenous synthetic LXR ligands activated the LXR program in monocyte-derived DCs ( 36,37 ). However, our data provide fi rst evidence that LXR-␣ can be transcriptionally active in the presence of IL-17A without exogenously added synthetic ligands.…”
Section: Discussionmentioning
confidence: 51%
“…Monocyte-derived dendritic cells (MDDCs) differentiated in the presence of LXR agonists prior to stimulation with TLR ligands released more chemokines and cytokines and showed increased capacity to elicit CD4 + T-cell proliferation [26]. In this case, LXR ligands were replenished regularly throughout differentiation.…”
Section: Responses To Inflammatory Stimulimentioning
confidence: 99%